Nitric oxide permits hypoxia-induced lymphatic perfusion by controlling arterial-lymphatic conduits in zebrafish and glass catfish - Dahl Ejby Jensen, Lasse (National Academy of Sciences, 2009)
The blood and lymphatic vasculatures are structurally and functionally coupled in controlling tissue perfusion, extracellular interstitial fluids, and immune surveillance. Little is known, however, about the molecular mechanisms that underlie the regulation of bloodlymphatic vessel connections and lymphatic perfusion. Here we show in the adult zebrafish and glass catfish (Kryptopterus bicirrhis) that blood-lymphatic conduits directly connect arterial vessels to the lymphatic system. Under hypoxic conditions, arterial-lymphatic conduits (ALCs) became highly dilated and linearized by NO-induced vascular relaxation, which led to blood perfusion into the lymphatic system. NO blockage almost completely abrogated hypoxia-induced ALC relaxation and lymphatic perfusion. These findings uncover mechanisms underlying hypoxia-induced oxygen compensation by perfusion of existing lymphatics in fish. Our results might also imply that the hypoxia-induced NO pathway contributes to development of progression of pathologies, including promotion of lymphatic metastasis by modulating arterial-lymphatic conduits, in the mammalian system.